Enterprises Performance Through Internal Resource Integration And Market Orientation Based On Competitive Advantages - Purwohandoko Purwohandoko (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2018)
Every company tries to achieve goals to gain profit and win the competition. To achieve this goal, the company must be able to demonstrate a competitive advantage. Therefore, the company always strives to gain competitive advantage by identifying, managing and optimizing their internal resources in the form of tangible and intangible assets that have superior characteristics as the power of generating competitive advantage. The sustainable competitive advantage by empowering their internal company resources can be defined as Research-Based View (RBV). The importance of research based views is contradicting with Market Based View (MBV) which stated that the more market oriented the more superior their competitive position. By using qualitative research (literature review), this study aims to understand and investigate how to create company performances through both point of views which is internal resources integration and market orientation based on competitive advantages.